Legal Interpretations of Qada Rawatib Prayers at Forbidden Times: Tarjih Analysis on the Badai’ as-Sanai’ fi Tartib asy-Syarai’ and al-Majmu’ Syarh al-Muhazzab - Dina, Dianita Rahma (Al-Mazaahib: Jurnal Perbandingan Hukum, 2024)
In an explicit manner, scholars have explained the ruling on performing qada rawatib prayers at forbidden times. However, some of the main fiqh books used as references do not clearly elaborate on the process of legal istinbat, such as how they chose the propositions used as the basis for the law. Essentially, the Prophet used to pray the ba'diyah zuhr prayer at a forbidden time (after 'asr). This narration is interpreted differently by Hanafiah and Shafi'iyah scholars with different arguments and corroborating evidence. This article aims to examine the reasons for the differences in the ruling on the ba'diyah zuhr prayer performed after 'asr, to find the similarities and differences, which are contained in the book Badai' as-Sanai' fi Tartib ash-Sharai' and the book al-Majmu' Syarh al-Muhazzab from the perspective of tarjih. This article is a literature research with a comparative analysis of the both books as the main source. The approach used is usul fiqh, more specifically the theory of tarjih in ta'arud al-adillah. On the basis of the tarjih analysis, the article finds that in Badai' as-Sanai' fi Tartib ash-Sharai', the qada of the zuhr ba'diyah prayer performed after 'asr is not allowed, with the argument that the hadith narration of Umm Salamah is specific to the Prophet. Meanwhile, in al-Majmu' Syarh al-Muhazzab, it is allowed to qada the prayer. These two books both use the tarjih method to produce these rulings with the enhancement of different arguments so that it affects the resulting law. This article contributes to the understanding of the legal istinbat method of qada of rawatib prayers at forbidden times from the perspective of ushul fiqh. Secara eksplisit, para ulama telah menjelaskan hukum melaksanakan qada salat rawatib di waktu terlarang. Meskipun begitu, beberapa kitab fikih induk yang dijadikan rujukan tidak merinci secara jelas mengenai proses istinbat hukum, seperti bagaimana mereka memilih dalil yang dijadikan dasar hukum. Pada dasarnya, Nabi pernah melaksanakan salat ba’diyah zuhur di waktu terlarang (setelah asar. Riwayat ini dibaca secara berbeda oleh ulama Hanafiah dan Syafi’iyah dengan argument dan dalil penguat lainnya. Artikel ini bertujuan untuk mengkaji sebab perbedaan hukum qada salat sunah ba’diyah zuhur yang dilakukan setelah asar, menemukan persamaan dan perbedannya, yang terkandung dalam kitab Badai’ as-Sanai’ fi Tartib asy-Syarai’ dan kitab al-Majmu’ Syarh al-Muhazzab dari perspektif tarjih. Artikel ini merupakan penelitian kepustakaan dengan analisis komparatif dari kedua kitab tersebut sebagai sumber utama. Pendekatan yang digunakan adalah usul fiqh, lebih spesifik teori tarjih dalam ta’arud al-adillah. Berdasarkan analisis tarjih, artikel ini menemukan bahwa dalam kitab Badai’ as-Sanai’ fi Tartib asy-Syarai’, qada salat ba’diyah zuhur yang dilakukan setelah asar tidak diperbolehkan, dengan argumen bahwa riwayat hadis Ummu Salamah merupakan kekhususan bagi Rasulullah. Sedangkan dalam kitab al-Majmu’ Syarh al-Muhazzab, diperbolehkan mengqada salat tersebut. Kedua kitab ini sama-sama menggunakan metode tarjih untuk menghasilkan hukum-hukum tersebut dengan penguatan dalil yang berbeda sehingga berpengaruh pada hukum yang dihasilkan. Artikel ini berkontribusi pada pemahaman metode istinbat hukum qada salat rawatib di waktu terlarang dari perspektif ushul fiqh.